Pengaruh penerapan anggaran berbasis kinerja, pengelolaan keuangan daerah, dan akuntabilitas publik terhadap kinerja keuangan pemerintah daerah - Aldi Ramadhan, Muhammad; Hendratno , Hendratno (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The purpose of this study is to determine the impact of performance-based budgeting, local financial management and public accountability practices in addressing government performance in the SKPD of Deli Serdang district in 2021. This research method uses quantitative methods. The population used in this study was SKPD personnel from the Delhi Serdang Regency government. The sample for this study consisted of 90 SKPD personnel or employees who were surveyed from 3 individuals per SKPD. Data collection techniques were performed using literature review and documentation. The processed data becomes the primary data. The analytical method used was multiple linear data regression using SPSS 23 software, and the results of this study demonstrate that the variable indicators tested influence local government performance. The variable indicators at issue are performance-based budgeting, local financial management, and public accountability. The results of this discovery are expected to provide insight and knowledge about the factors affecting local government performance. Furthermore, this study is expected to provide additional input and relevant evaluation material. Deli Serdang Regency Government Performance Evaluation and Future Guidelines.